The Impact of the Policy for Forming Religious Moderation Villages on Creating Peaceful Conditions in Southeast Sulawesi - Rahmad; Nasrullah Sulaiman; Muh. Yahya (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This study examines the implementation of the Religious Moderation Village (KMB) policy in Southeast Sulawesi Province as a response to digital disruption that threatens credible religious authority and trigger identity polarization. Amidst the contestation of digital spaces dominated by exclusive narratives and provocative hoaxes, the role of Islamic Religious Counselors is crucial as information mediators and agents of moderation. The main focus of this study is to evaluate the impact of the KMB policy in creating peaceful conditions and how the transmission of moderation values ​​is carried out in digital and non-digital contexts. The research methodology used is descriptive qualitative with a policy study approach. Data were collected through in-depth interviews with Islamic Religious Counselors and community leaders in the KMB area, participant observation of counseling activities, and content analysis on social media channels (Facebook, Instagram, YouTube, and TikTok) to measure the effectiveness of counter-narratives against extremist ideologies. The analytical framework uses Heidi Campbell's Religious-Social Shaping of Technology theory to dissect the shift in religious authority in the digital era. The research findings show that the establishment of the KMB in Southeast Sulawesi significantly strengthened social capital and the resilience of rural communities to asymmetric information. Religious instructors play a strategic role in enhancing the community's digital literacy to filter out misleading